Analisis Kemampuan Komunikasi Matematis Siswa Kelas VIII SMP Negeri 1 Sumpiuh ditinjau dari Self Confidence - Angela, Hilda; Ahmad, Ahmad (Peneliti.net, 2024)
The aim of this research is to analyze the mathematical communication ability of grade VIII students at SMP Negeri 1 Sumpiuh (State Junior High School 1 of Sumpiuh) in terms of self-confidence. The research employs a qualitative descriptive approach. In this study, there are three categories of self-confidence: high, moderate, and low. Each category consists of three students who are the subjects of the research. Data collection methods in this study include self-confidence questionnaires, mathematical communication ability tests, and interviews. The results of this study indicate that students with high self-confidence are capable of explaining using their own language effectively, presenting explanations in the form of drawings, solving mathematical problems, and expressing mathematical issues occurring in daily life in a mathematical form, although there are some mistakes. Students with moderate self-confidence can explain adequately in their own language, present explanations in the form of drawings, and partially solve mathematical problems, and they can express mathematical issues in daily life in a mathematical form, although not entirely accurate. Some students with low self-confidence can explain reasonably well in their own language, present explanations in the form of drawings, partially solve mathematical problems with errors, and express mathematical issues in daily life in a mathematical form, but not accurately.